Analyzing Administrative Service Quality: A Case Study Of A Regional Secretariat - Djoly Vekky Warokka; Ressy Mewengkang; Brain Fransisco Supit (Academy of Education Journal, 2026)
Administrative service delivery remains one of the most visible measures of government performance, yet local bureaucracies in Indonesia continue to struggle with translating formal procedures into consistent, citizen-centered practice. This study examines the quality of administrative services, particularly the handling of incoming and outgoing correspondence, at the Administrative Service Unit (Unit Layanan Administrasi/ULA) of the General Bureau, Regional Secretariat of North Sulawesi Province, and identifies the factors that constrain optimal service delivery. A descriptive qualitative approach was employed, guided by an interactive analytical model of data collection, reduction, display, and conclusion drawing. Data were gathered through in-depth interviews with key informants, direct observation, and documentation review, with credibility established through source and method triangulation. The findings show that consistent application of standard operating procedures, supported by electronic queuing systems and online document-tracking platforms, has meaningfully improved timeliness, accuracy, and transparency. However, service quality remains constrained by uneven staff understanding of procedural detail, ageing infrastructure, unstable internet connectivity, and workload imbalances relative to staff numbers. Courtesy, complaint responsiveness, and physical comfort were found to be strong contributors to public trust, even as budgetary and spatial limitations persist. The study concludes that sustainable improvement in administrative service quality requires an integrated strategy combining continuous staff training, infrastructure renewal, and adaptive procedural review. These findings offer practical implications for regional secretariats seeking to strengthen bureaucratic responsiveness and provide a contextual basis for future research on digital-era public service reform in Indonesia's subnational governments.